Sustainability and accountability of social enterprise / Nur Hayati Ab Samad ... [et al.] - Ab Samad, Nur Hayati; Arshad, Roshayani; Asat, Siti Haliza; Kasim, Nawal (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
Sustainability and accountability are pervasive issues for social entrepreneurial non-profit organisations (NPOs), which are also known as social enterprises as they seek to balance their social mission with financial responsibility. With the increased in the scope and size of the social enterprise, there is also increased need for accountability and organisational sustainability. Thus, in order to successfully fulfil these needs, social enterprises need to identify the relevant factors of sustainability that relates closely with accountability and organisational performance. This study aims to examine the extent social enterprise's sustainability based on the factors identified using self-constructed sustainability index. The four main factors are leadership capacity, adaptive capacity, management and technical capacity and financial viability. Content analysis was used to measure the sustainability index from the information disclosed in the annual reports by 210 organisations registered under the Registry of Societies (ROS) in Malaysia for the year 2010. Findings from the study indicates that most of the social enterprises are aware that effective leadership is vital for organisational sustainability. However, management and technical aspects tend to be neglected possibly due to lack of adequate resources and facilities to adapt to current changes. Overall, this study highlights that in order to survive in the future, the social enterprise need to appropriately address relevant factors that influence financial accountability and organisational sustainability especially on management and technical aspect in order to survive in the future.